A Field Trip That’s Not About the Destination but the Journey - Vanessa Scanfeld; Eric James; Vincent Dotoli (Middle Grades Review, 2023)
This Practitioner Perspective presents a middle school unit focused on designing a day-long field trip as an effective project-based initiative for advancing social and emotional learning (SEL). It considers the social and emotional competencies students develop as they navigate the complexities of this project: researching options, planning an itinerary that meets various parameters, and ultimately taking the trip. It also offers practical guidance to schools for successfully adopting this program.
Keywords: social and emotional learning; SEL; project-based learning; PBL; middle school